THE SECRET OF POLITICAL LEADERS’ PERSONAL APPEAL: (HOW) DO PERSONALITY TRAITS MATTER? - Kavaliauskaitė, Jūratė (Baltic Journal of Political Science, 2015)
Literature on personalization of politics emphasizes growing salience of individuals and private issues when party democracy is in decline. These trends are believed to strengthen personal appeal of politicians. However, what is the secret of party-leader’s personal appeal? Are politician’s personal traits the major key to popular sympathies? The article examines the impact of voter’s perception of party-leader’s personality along Big Five and personal charm on voter’s affinity for the leader. Analysis of the Lithuanian pre-election survey data (2012) on national party-leaders’ popular appeal, measured with “feeling thermometer”, and popular perception of leaders’ personality traits, measured with a set of semantic differentials, reveals that the significance of personality differs both across personality dimensions and between politicians under consideration. Agreeableness is the most important and universally desirable dimension of a political leader’s personality, followed by conscientiousness, with classic predictors of electoral choice under control. The significance of other personality dimensions of Big Five is much smaller if any, and personal charm seems to be inwrought with the five personality dimensions. The results prove that popular yearning for moral leadership, complemented with high performance, persists regardless of changes in political communication and (post)modern citizenship.